Axonal connections between S1 barrel, M1, and S2 cortex in the newborn mouse - Gellért, Levente; Luhmann, Heiko J.; Kilb, Werner (Frontiers in Neuroanatomy, 2023)
The development of functionally interconnected networks between primary (S1), secondary somatosensory (S2) and motor (M1) cortical areas requires coherent neuronal activity via corticocortical projections. However, the anatomical substrate of functional connections between S1 and M1 or S2 during early development remains elusive. In the present study, we used ex-vivo carbocyanine dye (DiI) tracing in paraformaldehyde-fixed newborn mouse brain to investigate axonal projections of neurons in different layers of S1 barrel field (S1Bf), M1 and S2 towards the subplate (SP), a hub layer for sensory information transfer in the immature cortex. In addition, we performed extracellular recordings in neocortical slices to unravel the functional connectivity between these areas. Our experiments demonstrate that already at P0 neurons from the cortical plate (CP), layer 5/6 (L5/6) and the SP of both M1 and S2 send projections through the SP of S1Bf. Reciprocally, neurons from CP to SP of S1Bf send projections through the SP of M1 and S2. Electrophysiological recordings with multi-electrode arrays in cortical slices revealed weak, but functional synaptic connections between SP and L5/6 within and between S1 and M1. An even lower functional connectivity was observed between S1 and S2. In summary, our findings demonstrate that functional connections between SP and upper cortical layers are not confined to the same cortical area, but corticocortical connection between adjacent cortical areas exist already at the day of birth. Hereby, SP can integrate early cortical activity of M1, S1 and S2 and shape the development of sensorimotor integration at an early stage.